DAMPAK WANITA KARIR BAGI KELUARGA PERSPEKTIF HUKUM ISLAM - Edy Setyawan; Adang Djumhur; Astri Nurhayati Triana Dewi (Mahkamah : Jurnal Kajian Hukum Islam, 2022)
The position between men and women should not be a common thing, even the difference between men and women in work is no longer in question, so women are no longer considered, so women are no longer considered as figures in charge of taking care of children, husbands and households only. In accordance with the development of the times make society change its perspective on the role and position of women who are in the midst of society, so many men and women who have careers in modern life many women can work and have a career well in social, cultural, economic and political. The study aims to answer the question that formulaizes the problem: "how does women impact careers on families of Islamic legal perspectives." This study uses qualitative research, data collected by observation, interview (interview), documentation then analyzed with descriptive methods of analysis. As for the results of this study: there are many factors that affect women's careers, one of which is because they want to help in pre-economic and obligation issues. There are also negative and positive impacts of career women for the family one of the negative impacts is the lack of time of the wife with the family, and less socializing with the surrounding community. Its positive impact helps in pre-economic, and enhances insight. Islam does not forbid women to make a career as long as it does not cause madaratan but if women have a career with the reason to hoard as much wealth as they do not pay attention to the things that are forbidden by the Shari'ah then obviously the woman of the career is forbidden.